Investigation of a Radio-Iodinated Alpha-Mangostin for Targeting Estrogen Receptor Alpha (ERα) in Breast Cancer: In Silico Design, Synthesis, and Biological Evaluation - Muchtaridi M; Nurhidayah W; Fakih TM; Kannaka K; Suzuki H; Subroto T; Uehara T (Dove Medical Press, 2024)
Muchtaridi Muchtaridi,1,2 Wiwit Nurhidayah,1 Taufik Muhammad Fakih,1,3 Kento Kannaka,4 Hiroyuki Suzuki,4 Toto Subroto,5 Tomoya Uehara4 1Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Research Collaboration Centre for Radiopharmaceuticals Theranostic, National Research and Innovation Agency (BRIN), Sumedang, 45363, Indonesia; 3Department of Pharmacy, Faculty of Mathematics and Natural Sciences, Universitas Islam Bandung, Bandung, 40116, Indonesia; 4Graduate School of Pharmaceutical Sciences, Chiba University, Chiba, 260-8675, Japan; 5Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Tomoya Uehara; Muchtaridi Muchtaridi, Email tuehara@chiba-u.jp; muchtaridi@unpad.ac.idIntroduction: Alpha-mangostin (AM), the most representative xanthone derivative isolated from the rind of the Purple Mangosteen (Garcinia mangostana Linn), has been reported pharmacologically to be associated with breast cancer in silico, in vitro, and in vivo. Although the pharmacological effects of AM are believed to involve the estrogen receptor alpha (ERα), there are no reports available in the literature describing the binding of AM to ERα.Methods: In this study, iodine-125 (125I)-labeled AM ([125I]I-AM) was prepared, and its binding to ERα was investigated in vitro using MCF-7 cell lines. To investigate the applicability of radioiodine-labeled AM as a radiopharmaceutical for breast cancer, [125I]I-AM was injected into nude mice bearing MCF-7.Results: The results obtained showed that the uptake of [125I]I-AM into MCF-7 cells was found to be inhibited by AM and tamoxifen, suggesting that its uptake is partially mediated by ERα. In addition, the biodistribution studies using MCF-7 bearing nude mice showed that [125I]I-AM accumulated in tumor tissues, although deiodination did occur, reducing the concentration of iodine-125 (125I) in the targeted cells.Conclusion: These results suggested that AM would be a useful platform for the development of a new radiopharmaceutical targeting ERα. Further studies are, however, required to reduce deiodination of [125I]I-AM in vivo.Keywords: alpha-mangostin (AM), estrogen receptor alpha (ERα), breast cancer, radiopharmaceutical, iodine-125 (125I)